Morphologically intact airways in lung fibrosis have an abnormal proteome - Jeremy A. Herrera; Lewis A. Dingle; M. Angeles Monetero; Rajamiyer V. Venkateswaran; John F. Blaikley; Felice Granato; Stella Pearson; Craig Lawless; David J. Thornton (Respiratory Research, 2023)
Abstract Honeycombing is a histological pattern consistent with Usual Interstitial Pneumonia (UIP). Honeycombing refers to cystic airways located at sites of dense fibrosis with marked mucus accumulation. Utilizing laser capture microdissection coupled mass spectrometry (LCM-MS), we interrogated the fibrotic honeycomb airway cells and fibrotic uninvolved airway cells (distant from honeycomb airways and morphologically intact) in specimens from 10 patients with UIP. Non-fibrotic airway cell specimens from 6 patients served as controls. Furthermore, we performed LCM-MS on the mucus plugs found in 6 patients with UIP and 6 patients with mucinous adenocarcinoma. The mass spectrometry data were subject to both qualitative and quantitative analysis and validated by immunohistochemistry. Surprisingly, fibrotic uninvolved airway cells share a similar protein profile to honeycomb airway cells, showing deregulation of the slit and roundabout receptor (Slit and Robo) pathway as the strongest category. We find that (BPI) fold-containing family B member 1 (BPIFB1) is the most significantly increased secretome-associated protein in UIP, whereas Mucin-5AC (MUC5AC) is the most significantly increased in mucinous adenocarcinoma. We conclude that fibrotic uninvolved airway cells share pathological features with fibrotic honeycomb airway cells. In addition, fibrotic honeycomb airway cells are enriched in mucin biogenesis proteins with a marked derangement in proteins essential for ciliogenesis. This unbiased spatial proteomic approach generates novel and testable hypotheses to decipher fibrosis progression.